Purification and properties of adenosine 5'-phosphosulphate sulphotransferase from Euglena. - Li, J Y (1991)
Adenosine 5'-phosphosulphate sulphotransferase (APSST) was extracted from Euglena gracilis Klebs var. bacillaris mutant W10BSmL by freezing and thawing and was purified about 10,000-fold (to homogeneity) with 10.5% recovery by (NH4)2SO4 precipitation, Sephadex G-100 chromatography, Reactive Blue-agarose, Reactive Dye-agarose, DEAE-cellulose, preparative isoelectric focusing and non-inactivating SDS/PAGE. The active APSST, with a molecular mass of 102 kDa and multiple forms from pI 5.0 to 5.5, is a tetramer held together by covalent (probably disulphide) bonds. An apparent Km of the purified enzyme for adenosine 5'-phosphosulphate (APS) of 0.1 microM is obtained when dithiothreitol is used as the thiol. The enzyme is stimulated by Mg2+, Ca2+ or Ba2+, and uses almost any thiol; dithiothreitol and dithioerythritol give the highest activity. In the absence of APS, the enzyme is inactivated (and is rendered monomeric) by thiols but is protected from thiol inactivation by AMP, adenosine 5'-phosphoramidate (APA) or adenosine 5'-monosulphate (AMS), which also inhibit APSST activity somewhat. The enzyme resists inactivation by SDS in the absence of thiols; SDS stimulates APSST activity at low concentration, but high concentrations are inhibitory.